Behavioural Finance: A Critical and Differential Study with Traditional Finance - Singhal, Roop Kishore (E-COMMERCE FOR FUTURE & TRENDS, 2023)
The study illustrated how traditional and behavioural finance principles affected investors' financial decisions regarding investments. Investors must understand behavioural finance to avoid making emotional financial judgements, even when sensible financial decisions are frequently made. In traditional finance investors get information and based on that they invest in different avenues. Largescale behavioural finance and conventional finance decisions of this kind can destabilise market oddities. The ideas of traditional finance and behavioural finance are briefly explained in this study attempt. Investor psychology, as well as human attitude and conduct, are the constant foundations of behavioural finance. In conventional finance, investors make decisions based on the data that is readily available in the market and on quantitative calculations of the market. Comparison of traditional finance versus behavioural finance to determine which approach to finance is best for investors. The conventional view of finance assumes that investors and the market act rationally by using all available information and possessing extensive knowledge. However, the behavioural finance perspective recognizes that investors' emotions and cognitive biases influence their decision-making processes, and that these decisions are influenced by different investment patterns. Additionally, behavioural finance acknowledges the existence of cognitive limitations and the constraints of arbitrage in financial markets. When the market is inefficient for making judgements, persons with cognitive biases will make decisions based on their skills and their ability to arbitrage. However, behavioural finance, which is based on social and cognitive psychology and aims to study actual investor behaviour in the financial markets, has come to convincingly show that investors make significant systematic errors and that psychological biases influence investors' investment decision-making. In other words, according to behavioural finance, investors frequently have psychological and emotional biases that cause them to make unwise financial decisions. In the first section of this article, an effort has been made to evaluate the type and breadth of knowledge regarding the theory of the efficiency of financial markets, one of the key paradigms in conventional finance. It has been vigorously debated recently despite its significant contribution to economic and financial theory. The second section focuses on behavioural finance theory, including the core theory (prospect theory), the main biases and heuristics, as well as the contribution and limitations of the field.